Behind visuals and sounds: A Barthesian semiotic analysis of virtual identity representation in the film colorful stage - Ammar Riski Januar; M. Fikri Akbar; Sandy Allifiansyah (Journal of Education, Social & Communication Studies, 2026)
This study explores the construction of virtual identity in the animated film Colorful Stage! A Miku Who Can’t Sing (2025) through Roland Barthes’ semiotic framework. Using a qualitative approach, the analysis focuses on selected visual and auditory signs, including stage design, avatar customization, audience responses, and glitch effects. Each sign is examined at the levels of denotation and connotation, followed by the identification of myths that naturalize particular understandings of digital identity. The findings demonstrate that the film portrays virtual identity as both aspirational and vulnerable: aspirational through the myth of perfection, where avatars appear flawless and empowering, and vulnerable through scenes that reveal emotional fragility and technological disruptions. This duality reflects broader cultural narratives about authenticity, social validation, and the tension between real and virtual selves. By situating the analysis within media semiotics and digital culture, the study highlights how Colorful Stage functions as a cultural text that mirrors contemporary discourses on identity in mediated environments.